Estimating the Impact of Technical Barriers to Trade in WTO Regime: The Case of Pakistan - Amir Mustafa; Ihtsham Ul Haq Padda; Sadia Safdar (NUST Journal of Social Sciences and Humanities, 2021)
Technical Barriers to Trade (TBT) forwarded by World Trade Organisation (WTO) has obstructed world trade patterns; generally, it is conceptualized as non-tariff barrier which impedes trade. In this study, impact of TBT on imports of Pakistan has been estimated. This paper explores how TBT affects import of Pakistan from its trade partner using PPML estimation method to handle zero trade flows and overdispersion of data of Pakistan’s import, based on gravity model. The findings depict that GDP of Pakistan and partners, exchange rate, tariff, distance, and contiguity are vital factors; along with TBT cases initiated by Pakistan have also impacted import from WTO members. The results suggest that Pakistan-initiated TBT and tariff have experienced lower import volume, hence they can be used to administer its ever-increasing trade deficit. The study also presents comparative analysis of TBT and tariff impacts on imports from high income, upper middle, lower middle, and lower income countries as classified by the World Bank.